Feasibility, reliability and validity of smartphone administered cognitive ecological momentary assessments in breast cancer survivors - Henneghan, Ashley M.; Paolillo, Emily W.; Van Dyk, Kathleen M.; Franco-Rocha, Oscar Y.; Patel, Mansi; Bang, So Hyeon; Moore, Raeanne C. (Frontiers in Digital Health, 2025)
ObjectiveBreast cancer and its treatment are associated with cancer-related cognitive impairments (CRCI). Cognitive ecological momentary assessments (EMA) allow for the assessment of individual subjective and objective cognitive functioning in real world environments and can be easily administered via smartphones. The objective of this study was to establish the feasibility, reliability, and validity of a cognitive EMA platform, NeuroUX, for assessing CRCI in breast cancer survivors.MethodsUsing a prospective design, clinical cognitive assessments (neuropsychological testing; patient reported outcomes) were collected at baseline, followed by an 8-week EMA smartphone protocol assessing self-reported cognitive concerns and objective cognitive performance via mobile cognitive tests once per day, every other day. Satisfaction and feedback questions were included in follow-up data collection. Feasibility data were analyzed using descriptive methods. Test–retest reliability was examined using intraclass correlation coefficients for each cognitive EMA (tests and self-report questions), and Pearson's correlation was used to evaluate convergent validity between cognitive EMAs and baseline clinical cognitive variables.Results105 breast cancer survivors completed the EMA protocol with high adherence (87.3%) and high satisfaction (mean 87%). Intraclass correlation coefficients for all cognitive EMAs were strong (>0.73) and correlational findings indicated moderately strong convergent validity (|0.23| < r < |0.61|).ConclusionFully remote, self-administered cognitive testing for 8-weeks on smartphones was feasible in breast cancer survivors who completed adjuvant treatment and the specific cognitive EMAs (cognitive EMA tests and self-report questions) administered demonstrate strong reliability and validity for CRCI.